Mutations of tyrosine 467 in the human norepinephrine transporter attenuate HIV-1 Tat-induced inhibition of dopamine transport while retaining physiological function - Matthew J. Strauss; Katherine D. Porter; Pamela M. Quizon; Sarah E. Davis; Steven Lin; Yaxia Yuan; Gustavo A. Martinez-Muniz; Wei-Lun Sun; Chang-Guo Zhan; Jun Zhu (PLoS ONE, 2022)
Dysregulation of dopaminergic transmission induced by the HIV-1 transactivator of transcription (Tat) has been implicated as a central factor in the development of HIV-1 associated neurocognitive disorders (HAND). We have demonstrated that the tyrosine470 residue of the human dopamine transporter (hDAT) plays a critical role in Tat-hDAT interaction. Based on the computational modeling predictions, the present study sought to examine the mutational effects of the tyrosine467 residue of the human norepinephrine transporter (hNET), a corresponding residue of the hDAT tyrosine470, on Tat-induced inhibition of reuptake of dopamine through the hNET. Mutations of the hNET tyrosine467 to a histidine (Y467H) or a phenylalanine (Y467F) displayed similar kinetic properties of reuptake of [3H]dopamine and [3H]norepinephrine in PC12 cells expressing wild-type hNET and its mutants. Compared to wild-type hNET, neither of Y467H or Y467F altered Bmax and Kd values of [3H]WIN35,428 binding, whereas Y467H but not Y467F decreased the Bmax of [3H]nisoxetine binding without changes in Kd. Y467H also increased the affinity of nisoxetine for inhibiting [3H]dopamine uptake relative to wild-type hNET. Recombinant Tat1-86 (140 nM) induced a significant reduction of [3H]dopamine uptake in wild-type hNET, which was attenuated in both Y467H and Y467F. Compared to wild-type hNET, neither Y467H or Y467F altered [3H]dopamine efflux in CHO cells expressing WT hNET and mutants, whereas Y467F but not Y467H decreased [3H]MPP+ efflux. These results demonstrate tyrosine467 as a functional recognition residue in the hNET for Tat-induced inhibition of dopamine transport and provide a novel insight into the molecular basis for developing selective compounds that target Tat-NET interactions in the context of HAND.